1994
DOI: 10.1007/bf00007976
|View full text |Cite
|
Sign up to set email alerts
|

Root growth and nitrate utilization of maize cultivars under field conditions

Abstract: In a 2-year field study conducted on a high fertilized Gleyic Luvisol in Stuttgart-Hohenheim significant differences among 10 maize cultivars were observed in soil nitrate depletion. The different capability of the cultivars to utilize nitrate particularly from the subsoil was positively correlated with (a) shoot N uptake at maturity, and (b) root length density (Lv) in the subsoil layers at silking. "Critical root length densities" for nitrate uptake were estimated by (a) calculating uptake rates per unit roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
3
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(100 citation statements)
references
References 28 publications
4
92
3
1
Order By: Relevance
“…Kristensen and Thorup-Kristensen (2004a) reported that soil N depletion by catch crop species was highly correlated with their rooting depth but there was little correlation with root density. According to Wiesler and Horst (1994), sweet corn roots may penetrate the soil to a depth of 1.5 m. However, Kristensen and Thorup-Kristensen (2004b) observed shallow rooting (0.3 m) by sweet corn in minirhizotrons and they attributed the differences in their results to relatively low temperatures in spring and summer. In our experiment sweet corn rooting depth approached 1.1 m, which was in accordance with the results of Ren (2003) at Dongbeiwang in the Beijing suburbs.…”
Section: Discussionmentioning
confidence: 99%
“…Kristensen and Thorup-Kristensen (2004a) reported that soil N depletion by catch crop species was highly correlated with their rooting depth but there was little correlation with root density. According to Wiesler and Horst (1994), sweet corn roots may penetrate the soil to a depth of 1.5 m. However, Kristensen and Thorup-Kristensen (2004b) observed shallow rooting (0.3 m) by sweet corn in minirhizotrons and they attributed the differences in their results to relatively low temperatures in spring and summer. In our experiment sweet corn rooting depth approached 1.1 m, which was in accordance with the results of Ren (2003) at Dongbeiwang in the Beijing suburbs.…”
Section: Discussionmentioning
confidence: 99%
“…As root growth and maintenance are energetically costly, root architecture is a lever to optimize the balance between nitrogen absorption ability and metabolic cost (Lynch 2014). From this perspective, increasing the root surface by increasing fine root density has been considered as one possible strategy in other crops (White et al 2013) such as maize (Wiesler and Horst 1994), faba beans (Kage 1997), and Kentucky bluegrass (Sullivan et al 2000).…”
Section: Nitrogen Uptake Efficiency Must Be Improved To Maintain a Himentioning
confidence: 99%
“…Within the 'dry' treatment, plants might have acquired more N at elevated [COg] either because the soil remained wetter between waterings, or because of their greater root length density (e.g. Wiesler & Horst 1994), or both. This N was taken up from the top soil layers, which might reflect the extra stimulation of root growth in the top soil layers by elevated [CO2].…”
Section: Distribution Of Soil Inorganic N and Plant N Uptakementioning
confidence: 99%